Persistence of Helicobacter pylori in the oral cavity after systemic eradication therapy - E. C. E. Gebara (journal of clinical periodontology, 2006)
Aim: The present study aimed to evaluate if the oral cavity of chronic periodontitis patients can harbor Helicobacter pylori after systemic eradication therapy. Materials and Methods: Samples of 30 patients (15 with gingivitis and 15 with chronic periodontitis) positive for H. pylori in the stomach were evaluated. Samples were collected 3 months after triple systemic antibiotic therapy from saliva, microbiota from the dorsum of the tongue, supra- and sub-gingival plaque as well as gastric biopsies. DNA of each sample was extracted by the boiling method and used as a template in polymerase chain reaction with the primers JW22/23. Results: Eighteen patients (60%) harboured H. pylori in their mouths. Five patients (16.6%) were positive in saliva, two (6.6%) on the dorsum of the tongue, nine (30%) in supra-gingival plaque, 14 (46.6%) in sub-gingival plaque and three (10%) in the stomach. There was no statistically significant difference between study groups. Conclusion: Eradication of H. pylori after therapy was more effective for the stomach than for the mouth (po0.001). Mouths of patients with gingivitis or with chronic periodontitis, who are positive for H. pylori in their stomachs, may be considered as reservoirs of these bacteria.